PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS LINGKUNGAN UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR PADA MATERI PEMISAHAN CAMPURAN DAN ANALISIS DI SMK NEGERI 3 KABUPATEN BANTAENG - Akhmad Akhmad (Chemistry Education Review (CER), 2017)
This research is the development of (research and development), which includes the development of learning tools that is devoted to the development of learners' worksheets (LKPD) for material separation and analysis on Learners class XII SMK Negeri 3 Bantaeng Bantaeng. Development procedures used in this study is a model Thiagarajan consisting of four stages: define, design, develop and disseminate or adapted into a 4-D model is the definition, design, development and deployment. LKPD based environments are developed, validated by experts and practitioners and has undergone minor revisions to obtain decent results used. The results showed that the device STAD cooperative learning are valid, practical and effective. Worksheet learners (LKPD) used met the criteria of validity, namely the category of "very valid". Additional learning tools are validated as supporting data, including books learners (BPD), and the lesson plan (RPP) is in the category "Valid". LKPD used otherwise practical for LKPD implemented entirely in the category and the response of teachers gave a positive response. LKPD said to be effective because it has met the criteria of effectiveness, with the results: (1) The teacher is able to manage the learning process with a very high category; (2) The students become more active in the learning process, it seemed that all the categories on the activity of learners are met; (3) Activities teachers in all categories are met; (4) The test results of all students study had an average score of 81.47 out of 100 with learners who pass the study 22 people or 88%; (5) In general, learners are motivated after attending a lesson in both categories; (6) The students responded positively to LKPD used.